Effect of ammonium thiocyanate on ionic conductivity and thermal properties of polyvinyl alcoholâmethylcelluloseâbased polymer electrolytes - Shamsuri, N.A. (Springer Science and Business Media Deutschland GmbH, 2020)
In this work, a polymer blendâbased electrolyte system using polyvinyl alcohol (PVA) and methylcellulose (MC) in the weight ratio of 50:50 as hosts and ammonium thiocyanate (NH4SCN) as dopant salt has been prepared and characterized. Fourier transform infrared spectroscopy (FTIR) studies indicate that functional groups containing oxygen atom in both polymers have interacted with each other. Complexation between the polymer hosts and dopant salt is confirmed from the shifting of hydroxyl band and SCN- band. Phenomena of ion association and ion dissociation have been analysed by deconvoluting the FTIR band between 2030 and 2090 cmâ1. Sample with 40 wt NH4SCN achieves the highest ambient conductivity of (1.45 Â± 0.51) Ã 10-4 S cm-1. It is inferred that the conductivity is mainly governed by the diffusion coefficient and mobility of charge carriers. It is found that the increase in conductivity is accompanied by a decrease in the glass transition temperature (Tg). The variation of conductivity can be verified by the results from field emission scanning electron microscopy (FESEM). Â© 2020, Springer-Verlag GmbH Germany, part of Springer Nature.